2013
DOI: 10.1007/s00425-013-1964-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of NF-Y transcription factor families in Canola (Brassica napus L.)

Abstract: NF-Y (NUCLEAR FACTOR-Y), a heterotrimeric transcription factor, is composed of NF-YA, NF-YB, and NF-YC proteins in yeast, animal, and plant systems. In plants, each of the NF-YA/B/C subunit forms a multi-member family. NF-Ys are key regulators with important roles in many physiological processes, such as drought tolerance, flowering time, and seed development. In this study, we identified, annotated, and further characterized 14 NF-YA, 14 NF-YB, and 5 NF-YC proteins in Brassica napus (canola). Phylogenetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 70 publications
7
38
1
3
Order By: Relevance
“…In mammals, invertebrates, and fungi, there are one or two genes coding for each subunit. Instead, plants have dramatically expanded the number of NF-Y genes: Typically, there are 8 to 14 gene family members for each subunit, conferring an enormous combinatorial capacity on the trimer; some are expressed in a tissue-restricted manner, and many are relatively ubiquitous (Gusmaroli et al, 2001(Gusmaroli et al, , 2002Stephenson et al, 2007;Siefers et al, 2009;Cao et al, 2011b;Hilioti et al, 2014;Liang et al, 2012Liang et al, , 2014Quach et al, 2015;RĂ­podas et al, 2015;Zhang et al, 2015;Qu et al, 2015;Feng et al, 2015;Ren et al, 2016;Malviya et al, 2016;Li et al, 2016;Yang et al, 2016;Zhang et al, 2016). Typical features of other plant TFs, such as the presence of duplicate members with similar functions and neofunctionalization of specific genes, were determined by genetic experiments, mostly performed in Arabidopsis thaliana (reviewed in Laloum et al, 2013;Petroni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, invertebrates, and fungi, there are one or two genes coding for each subunit. Instead, plants have dramatically expanded the number of NF-Y genes: Typically, there are 8 to 14 gene family members for each subunit, conferring an enormous combinatorial capacity on the trimer; some are expressed in a tissue-restricted manner, and many are relatively ubiquitous (Gusmaroli et al, 2001(Gusmaroli et al, , 2002Stephenson et al, 2007;Siefers et al, 2009;Cao et al, 2011b;Hilioti et al, 2014;Liang et al, 2012Liang et al, , 2014Quach et al, 2015;RĂ­podas et al, 2015;Zhang et al, 2015;Qu et al, 2015;Feng et al, 2015;Ren et al, 2016;Malviya et al, 2016;Li et al, 2016;Yang et al, 2016;Zhang et al, 2016). Typical features of other plant TFs, such as the presence of duplicate members with similar functions and neofunctionalization of specific genes, were determined by genetic experiments, mostly performed in Arabidopsis thaliana (reviewed in Laloum et al, 2013;Petroni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…VfNF-YB5 grouped with AtNF-YB8/10. A previous study reported that AtNF-YB1/8/10 shares high similarities with OsHAP3A/ B/C (Liang et al 2014). Silencing of OsHAP3A by an antisense construct led to chloroplast-related abnormalities (Miyoshi et al 2003).…”
Section: Arabidopsis Thalianamentioning
confidence: 93%
“…For example, there are at least 10 NF-YB genes in Arabidopsis, (Edwards et al 1998;Gusmaroli et al 2001Gusmaroli et al , 2002, 11 NF-YB genes in wheat (Triticum aestivum) and rice (Stephenson et al 2007;Thirumurugan et al 2008), and 17 NF-YB genes in Brachypodium (Cao et al 2011). Recently, 14 NF-YB genes have been identified and characterized in canola (Liang et al 2014) and 32 NF-YB genes in soybean (Quach et al 2014). The occurrence of multi-member gene families in plants suggests that there is genetic redundancy or functional divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the NF-Y subunit also plays an important role in response to stress, such as drought stress [20][21][22][23][24][25]. It is worth noting that more and more studies have found that the NF-Y subunit participates in the photoperiodic regulation of flowering induction pathways, and that different subunits function differently [26][27][28][29][30][31][32][33][34]. For example, Cai et al found that the AtNF-YB2 promotes the flowering process by increasing expression of the flowering key genes FLOWER-ING LOCUS T (FT) and SUPPRESSOR OF OVER EXPRESSION OF CONSTANS1 (SOC1) [27].…”
Section: Introductionmentioning
confidence: 99%